ASSOCIATION BETWEEN ROTAVIRUS AND THE PRESENCE OF DIARRHEA IN PIGLETS FROM INTENSIVE PIG FARMS - Rojas M., Miguel (2011)
The objective of the study was to determine the frequency of rotavirus and itsassociation with the occurrence of diarrhea in piglets reared in two intensive pig farms inLima valley, Peru. The presence of rotavirus was determined by the identification of theviral genome using polyacrylamide gel electrophoresis (PAGE) in diarrheic (n=69) and non-diarrheic (n=73) fecal samples from 1 to 4 week-old piglets. The case-controlepidemiological design was used to establish the association between the occurrence ofdiarrhea and the presence of rotavirus in feces, using a multiple logistic regression (typeof feces, age, and origin). The frequency of porcine rotavirus group A in diarrheic stoolsamples from pig farm 1 was 41.4% (12/29) and from pig farm 2 was 16.6% (4/24), and onepositive was found in non diarrheic stool from each pig farm. The presence of porcinerotavirus versus occurrence of diarrhea, adjusted to potential confusing variables (ageand origin) resulted in an Odds Ratio of 12.6 with a confidence interval between 2.7 and59.3%. Additionally, two segments of RNA from the genome of porcine Picobirnaviruswere found. It is concluded that the presence of porcine rotavirus represents a risk factorfor the presentation of diarrhea in newborn piglets from intensive pig farms in Lima.